2020
DOI: 10.1525/collabra.310
|View full text |Cite
|
Sign up to set email alerts
|

Do Incidental Environmental Anchors Bias Consumers’ Price Estimations?

Abstract: It is well-established that decision makers bias their estimates of unknown quantities in the direction of a salient numerical anchor. Some standard anchoring paradigms have been shown to yield pervasive biases, such as Tversky and Kahneman's (1974) classic 2-step task which includes a comparative question followed by an estimation question. In contrast there is much less evidence for the claim that incidental environmental anchors can produce assimilative effects on judgments, such as the amount people are wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
1
16
2
3
Order By: Relevance
“…We believe that replication studies are necessary for the progress of anchoring research: We provide evidence that points to questionable research practices in subliminal anchoring research, which dovetails with findings by Shanks et al (2020) regarding incidental environmental anchoring). Although we do not doubt the existence of classical anchoring effects, we advise researchers to use p-curve analyses and direct replications (e.g., Simonsohn et al, 2014 ) to test for the robustness of specific kinds of anchoring or moderators of anchoring.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We believe that replication studies are necessary for the progress of anchoring research: We provide evidence that points to questionable research practices in subliminal anchoring research, which dovetails with findings by Shanks et al (2020) regarding incidental environmental anchoring). Although we do not doubt the existence of classical anchoring effects, we advise researchers to use p-curve analyses and direct replications (e.g., Simonsohn et al, 2014 ) to test for the robustness of specific kinds of anchoring or moderators of anchoring.…”
Section: Discussionsupporting
confidence: 57%
“…These two specific kinds of anchoring are similar in that they do not include the classical comparative question of anchoring (“Is it more or less than X?”), and for both, priming has been suggested as an explanation ( Brewer & Chapman, 2002 , p. 76, for IEA; Mussweiler & Englich, 2005 , p. 135, for subliminal anchoring). Interestingly, IEA could not be replicated either (e.g., Edmonds, 2017 ; Klein et al, 2018 ), and previous results have been interpreted as a possible result of questionable research practices ( Shanks, Barbieri-Hermitte, & Vadillo, 2020 ). However, the recent failures to replicate IEA ( Klein et al, 2018 ; Shanks et al, 2020 ) did not attempt to address the replicability of subliminal anchoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the irrelevant high anchor presented in the preceding task influenced the judgment. While some studies Chapter 13 9 have suggested such basic anchoring effects, more recent studies (Brewer & Chapman, 2002;Klein et al, 2018;Röseler et al, 2021;Shanks, Barbieri-Hermitte, & Vadillo, 2020) failed to replicate them, showing that subliminal anchoring is weaker and more fragile than other forms of anchoring.…”
Section: Paradigmsmentioning
confidence: 99%
“…While numeric priming offers a parsimonious explanation for some outcomes (Critcher & Gilovich, 2008;Wilson et al, 1996;Wong & Kwong, 2000), these effects are not robust (Brewer & Chapman, 2002;Klein et al, 2018;Röseler et al, 2021;Shanks et al, 2020), and numeric priming thus does not seem to play a significant role in most anchoring effects (Newell & Shanks, 2014).…”
Section: Theoretical Accountsmentioning
confidence: 99%